Supergene minerals in the Horni Slavkov uranium ore district, Czech Republic - Plasil,J.; Sejkora,J.; Ondrus,P.; Veselovsky,F.; Beran,P.; Golias,V. (Journal of the Czech Geological Society, 2006)
This paper presents the existing and newly obtained information on supergene minerals of the Horni Slavkov uranium ore district. Mineralogical studies confirmed occurrences of the following minerals: anglesite, annabergite, arsenolite, autunite, carnotite, compreignacite, cuprosklodowskite, kaatialaite, liebigite, meta-autunite, metanovacekite, metatorbernite, mohrite, novacekite, phosphuranylite, rutherfordine, schultenite, siderite, torbernite, uranophane, zeunerite, and unnamed phase UNK5. The present study did not confirm the presence of previously reported occurrences of bassetite soddyite, uranophane-β and uranospinite. Also presented is interpretation of formation of the icsupergene mineralization in this ore district.
Keywords: Horni Slavkov uranium district; supergene minerals; uranium; uranyl minerals